PENGARUH DANA PIHAK KETIGA TERHADAP PENYALURAN DANA PERBANKAN SYARIAH DI SUMATERA BARAT - Gampito, Gampito (JURIS (Jurnal Ilmiah Syariah), 2014)
This research was aimed to know how significant the influence of the saving account (consisting of saving (tabungan), bill (giro), and…(deposito)) of third person toward supplying the Fund of “Syariah” Bank in West Sumatera. The data was seventeen “Syariah” banks in West Sumatera. “Syariah” Bank were became the object of this research that had three products: saving (tabungan), bill (giro), and fixed deposit (deposito). Through testing hyphotesis, the result of the research showed that those products had significant influences toward the supplying the Fund of “Syariah” Bank in West Sumatera. In this case, the management of supplying the Fund of “Syariah” Bank in West Sumatera had been successful in collecting the fund from “Syariah” Bank in West Sumatera. In detail, it was found that saving (tabungan) and fixed deposit (deposito) had significant influence toward supplying the Fund of “Syariah” Bank since 2008 up to 2011 in West Sumatera. Meanwhile, bill (giro) had no significant influence toward supplying the Fund of “Syariah” Bank in West Sumatera during observation.